From subsistence to resistance: Asylum-seekers and the other 'Occupy' in Hong Kong. (May 2018) - Vecchio, Francesco; Ham, Julie
In 2014, the Refugee Union – the only asylum-seeker-led organisation in Hong Kong – organised an eight-month-long protest against assistance policies and practices which they argued dehumanised and jeopardised their dignity and survival. Central to this public protest, termed 'Refugee Occupy', was the transformation of a traditional mechanism for asylum-seeker containment – the refugee camp – into a vehicle for asylum-seeker voice, participation and resistance. In this article, we discuss the asylum-seeker assistance policies and practices over the last decade that have resulted in a borderless refugee camp in Hong Kong. We explore the asylum-seekers' use of the camp concept and its spatial and political transformation into an instrument for asylum-seeker resistance and political engagement. We conclude by situating the Refugee Union's formation alongside other migrant-led social movements in Hong Kong and globally.